2020
DOI: 10.1039/c9ta11907h
|View full text |Cite
|
Sign up to set email alerts
|

Advanced hermetic encapsulation of perovskite solar cells: the route to commercialization

Abstract: An advanced laser-assisted sealing method was developed and used to hermetically encapsulate HTM-free perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…109 Remarkably, the device performance does not present significant degradation under those have implemented a laser-sealed glass-frit encapsulation on the C-PSCs which allowed for the cells to withstand damp-heat and thermal cycling tests (although they were carried out for less than 1000 h). 115 Wu et al have also conducted damp-heat tests on the non-encapsulated C-PSCs, where the authors observed that such cells are able to retain 77% of the initial PCE after such an intensive test. 116 Furthermore, due to the ease of carbon-based electrode deposition, large sized modules of 70 cm 2 have been fabricated, showing an extraordinary stable performance of perovskite modules even in humid environments.…”
Section: View Article Onlinementioning
confidence: 99%
“…109 Remarkably, the device performance does not present significant degradation under those have implemented a laser-sealed glass-frit encapsulation on the C-PSCs which allowed for the cells to withstand damp-heat and thermal cycling tests (although they were carried out for less than 1000 h). 115 Wu et al have also conducted damp-heat tests on the non-encapsulated C-PSCs, where the authors observed that such cells are able to retain 77% of the initial PCE after such an intensive test. 116 Furthermore, due to the ease of carbon-based electrode deposition, large sized modules of 70 cm 2 have been fabricated, showing an extraordinary stable performance of perovskite modules even in humid environments.…”
Section: View Article Onlinementioning
confidence: 99%
“…An advanced laser-assisted glass-frit encapsulation method was also developed to hermetically seal HTM-free PSCs. The PCE of the hermetically encapsulated devices remained constant for 500 h under humid air feeding exposure (80 ± 5% RH) while nonhermetically encapsulated devices degraded after 50 h [153]. In further tests, sealed devices passed 70 thermal cycles (−40 • C to 85 • C) and 50 h damp heat (85 • C, 85% RH) tests according to IEC61646 standards.…”
Section: Stability Studiesmentioning
confidence: 99%
“…One option is a laser-assisted hermetic glass frit encapsulation to seal HTL-free PSCs without the use of sealants. [133] However, it requires high processing temperature (120 C). Therefore, more in-depth studies are currently underway with the aim of developing a similar hermetic encapsulation procedure with processing temperature lower than 85 C to enable the use of highly efficient HTM-based devices (for devices with superior PCE) and reducing the high fabrication costs.…”
Section: Encapsulationmentioning
confidence: 99%
“…Therefore, more in-depth studies are currently underway with the aim of developing a similar hermetic encapsulation procedure with processing temperature lower than 85 C to enable the use of highly efficient HTM-based devices (for devices with superior PCE) and reducing the high fabrication costs. [127,133] Various commercial transparent polymer-based barriers have been investigated as device encapsulants for PSCs, among these are polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), poly(methyl methacrylate) (PMMA), and polycarbonate (PC). One of the main limitations is again the temperature of the thermoforming.…”
Section: Encapsulationmentioning
confidence: 99%